Protecting social security: The case against extending the full retirement age - Edward Lane (Levy Economics Institute of Bard College, 2025)
The Social Security "full retirement age" (FRA) is the age at which retirement income benefits are available without reduction for early commencement. Presently, that age is 67 for those born in 1960 or later. This paper is about the unfair and unnecessary threat to reduce Social Security retirement income benefits (Romig 2023) by extending the full benefit retirement age-a change that will affect upwards of 80 percent of future retirees (Ross 2024), most of whom can ill-afford the reduction (Romig 2023). For those who don't follow these issues closely, the Social Security retirement, or Old-Age & Survivors Insurance (OASI) Trust Fund is projected to become insolvent in 2033. 1 Without Congressional action to preserve scheduled benefits, payable benefits would then be reduced by 20-25 percent. 2 While both President Trump (Bolton 2024) and House Speaker Mike Johnson (Murray et al. 2025) have promised not to cut Social Security at a time when there is intense political pressure to reduce the federal budget deficit (Duehren 2025), it is unclear what will happen once Congress settles on a fiscal 2026 budget and the president signs off. If benefits are not reduced, the trust fund insolvency issue must still be resolved. To better understand why extending Social Security's FRA would be both unnecessary and unfair, this paper briefly explores Social Security's history, how Social Security payroll taxes subsidize other government expenditures, and how attempts are being made to roll back Social Security retirement benefit eligibility while other publicly funded retirement programs covering government employees have far more generous retirement eligibility provisions. The paper will conclude with recommendations to avoid program insolvency while preserving the FRA.
Keywords: H00; H50; H51; H53; H55; H61; H62; H63; H64; H21; H22; H23; H24; H31; E62; 330; Social Security; FICA; Taxes; Trust Funds; OASI; OASDI; Medicare; Deficit; Inflation; Welfare; Treasury; Old-age; Intragovernmental and Federal debt; Retirement age